Dakota [large type] - Grimes, Martha (Thorndike Press large print core, 2008)
Andi Oliver, an amnesiac and drifter, is hired by Klavan's, a massive pig farming facility that specializes in the dark art of modern livestock management. As Andi begins to uncover the truth about Klavan's, two men are on her trail, one a gunman hired to kill her, another who has followed her across three states demanding something from her forgotten past.